Simulation of self-ignition flame suppression for high-pressure hydrogen release using porous media - Haoran YANG; Gan CUI (You-qi chuyun)
ObjectiveTo enhance the safety of hydrogen use, the impact of porous media on the propagation dynamics and suppression of self-ignition flames during hydrogen release in pipes was investigated. MethodsA numerical model of a high-pressure hydrogen release pipeline segment with porous medium was established in Ansys Fluent, using the large eddy simulation model, the eddy dissipation concept model, a 21-step detailed hydrogen-air chemical reaction mechanism, and an isotropic porous material model. The simulation results were compared with prior research to ensure the accuracy of the numerical simulation and the reliability of the outcomes. ResultsAnalysis of pressure variations of the self-ignition flame in both the pipe and the porous medium revealed that the porous medium partially absorbed the pressure wave. Furthermore, when the shock wave entered the porous medium, reflected shock waves were generated, intersecting in front of the porous medium to create a high-pressure zone. Analysis of temperature variations in the porous medium, considering the cold wall effect, indicated that the porous material pipe has a greater specific surface area than ordinary pipes, leading to significant heat loss during flame propagation. The concentration distribution of OH radicals initially increased and then decreased, ultimately leading to quenching due to reduced activity caused by the wall effect of the porous medium. Both the release pressure of hydrogen and the porosity of the porous medium influenced the quenching distance of flames in the porous medium. Higher release pressure increased the quenching distance, while greater porosity weakened the porous medium’s flame suppression capability. ConclusionThe research can serve as a reference for the suppression mechanisms of porous media, the suppression of self-ignition flames in pipes, and safety measures for hydrogen release.